2012
DOI: 10.1108/09565691211222072
|View full text |Cite
|
Sign up to set email alerts
|

Understanding functions: an organizational culture perspective

Abstract: Purpose -This paper aims to discuss the disconnection between the recognized centrality of the functional approach to records management and archives and the actual understanding of functions that scholars, practitioners, and records creators seem to have. It suggests that records professionals should consider functions not in the abstract but in the specific socio-cultural contexts in which they are enacted. Design/methodology/approach -After analyzing the main theoretical and methodological issues concerning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 22 publications
1
31
0
2
Order By: Relevance
“…112-113). Previous studies and literature (Foscarini 2012;Orr 2005;Smith 2007, p. 54) show that records management professionals prefer functional classifications because they find it easier to manage records in the functional structure (Todd 2003, p. 3). In Foscarini (2012, p. 30), a belief in 'power of function' as such was also strong among records practitioners.…”
Section: Functional Classification Of Recordsmentioning
confidence: 93%
See 4 more Smart Citations
“…112-113). Previous studies and literature (Foscarini 2012;Orr 2005;Smith 2007, p. 54) show that records management professionals prefer functional classifications because they find it easier to manage records in the functional structure (Todd 2003, p. 3). In Foscarini (2012, p. 30), a belief in 'power of function' as such was also strong among records practitioners.…”
Section: Functional Classification Of Recordsmentioning
confidence: 93%
“…Functional terminology is vacillating, and different terms are used almost synonymously. Function, as a concept, is obscure (Foscarini 2012). Foscarini (2012) found that the meanings of functional concepts like ''function'', ''activity'' and ''transactions'' were not clear to professionals.…”
Section: Functional Classification Of Recordsmentioning
confidence: 98%
See 3 more Smart Citations